PERAN KOPERASI SERBA USAHA MUTIARA MANDIRI UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT GUNUNG SINDUR KABUPATEN BOGOR - Susilawetty, -; Supena, Karna (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2013)
The society consisted of entrepreneurs Gunung Sindur Bogor workers, mobile sellers and few others business with limited capital. Multipurpose Cooperative Enterprises Mutiara Mandiri role in improving the economy Gunung Sindur Bogor. Purpose of this study was to determine 1). How the role of Independent Multipurpose Cooperative Enterprises Mutiara Mandiri to boost the economy and society Gunung Sindur Bogor 2). To know is there any limiting factors in the management of the cooperative effort Multi Mutiara Mandiri. This research method is descriptive method that is normative and empirical research on the problems that occur at this time. The conclusion are: (1) The Cooperative Enterprises Mutiara Mandiri Gunung Sindur Bogor has a significant role in improving the welfare of society Gunung Sindur particularly the economical matters, especially members of the cooperative (2) The obstacles are: 1. Internally: (a) lack of understanding of the cooperative (b) lack of awareness of the cooperative meaning and procedures (c) Do not understand that the cooperative management. 2. externally: the limitation of the cooperative capital which cannot be used for loan and no fixed asset.